Strategies of Islamic Education Institutions in Fundraising Waqf to Create Economic Independence in the Era of the 4.0 Industrial Revolution - Syamsuri Syamsuri; Vina Fithriana Wibisono (At-Ta'dib, 2019)
In facing the current 4.0 industrial revolution, the role of digitalization-based waqf is very much needed in solving the problems of the social economy. One of the waqf-based educational institutions that implements waqf fundraising strategies with the nature of independence in creating an economy in the digitalization era is Pesantren in Indonesia. therefore the purpose of this research is to discuss the strategy of Islamic Education Institutions (IEI) in fundraising waqf in creating economic independence in the era of the 4.0 industrial revolution. The scope to be discussed covers aspects of management, distribution, and fundraising for endowments with the final goal referring to the willingness of the poor. The research method used is library research using conceptual approach. The results of this study indicate that the existence of a good waqf fundraising strategy undertaken by nadzir can indirectly improve the welfare of the people and can create economic independence. The strategies in waqf fundraising implemented by IEI are making long-term strategic program plans; designing a long-term budget; developing fundraising scenario (goals and strategies); identify the source of funds (waqif) through the direct and indirect method; and monitoring work results (monitoring and reporting) by reporting work results along with evaluations and future plans.